2020
DOI: 10.1002/bab.2066
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of iron oxide nanoparticles–antiubiquitin antibodies conjugates for depletion of dead/damaged spermatozoa from buffalo (Bubalus bubalis) semen

Abstract: The synthesis of iron oxide nanoparticles (IONPs)-antiubiquitin antibodies (Abs) complex for depletion of dead/damaged spermatozoa from buffalo semen was done. The IONPs synthesized were round in shape with size of 12.09 ± 0.91 nm. At the end of the two-step functionalization, that is, silanization and pegylation of bare IONPs and bioconjugation of functionalized IOPNs, particles with the sizes of 19.15 ± 1.46, 20.72 ± 0.95, and 73.01 ± 7.56 nm, respectively, were obtained. Twenty-four semen samples from four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The applicability of nanoparticles has been used to improve the selection of sperm, semen sexing, and cryopreservation in several species of farm animals (Bisla et al, 2020; Domínguez et al, 2018; Isaac et al, 2017). It is important to emphasize that their size, surface volume, composition, shape, and surface functionalization are very important for their efficiency, since different nanoparticles have different effects when exposed to sperm (Z. Li et al, 2015; Taylor et al, 2015; Truong et al, 2019).…”
Section: Effects Of Nanoparticles On Spermatozoa In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…The applicability of nanoparticles has been used to improve the selection of sperm, semen sexing, and cryopreservation in several species of farm animals (Bisla et al, 2020; Domínguez et al, 2018; Isaac et al, 2017). It is important to emphasize that their size, surface volume, composition, shape, and surface functionalization are very important for their efficiency, since different nanoparticles have different effects when exposed to sperm (Z. Li et al, 2015; Taylor et al, 2015; Truong et al, 2019).…”
Section: Effects Of Nanoparticles On Spermatozoa In Vitromentioning
confidence: 99%
“…Various studies reported that nanoparticles have been used to improve the selection of sperm, semen sexing, and cryopreservation (Bisla et al, 2020; Domínguez et al, 2018; Isaac et al, 2017), as well as to improve survival of preantral follicles (Karime et al, 2020) and COC maturation (Abdel‐Halim & Helmy, 2018). These observations indicate the potential of using nanomaterials to improve ART and emphasize the importance of knowing the recent advances about these smart nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPs have different applications in the field of medical and veterinary sciences. The emerging trends of using the NPs in the semen biology for various applications like depletion of dead/moribund and spermatozoa with various surface damages/alterations from the ejaculates (Nano‐purification of semen) (Odhiambo et al, 2014; Feugang et al, 2015; Durfey, Swistek, et al, 2017; Bisla, Rautela, et al, 2020; Bisla, Rautela, et al, 2021), bio‐imaging of gametes (Barchanski et al, 2015; Vasquez et al, 2016), sex‐sorting of semen (Domínguez et al, 2018; Moradi et al, 2021) and evaluation of male infertility using different biomarkers (Vidya & Saji, 2018) have opened the tremendous opportunities in the reproductive biology.…”
Section: Introductionmentioning
confidence: 99%
“…NPs after bio‐conjugation with various negative fertility biomarkers like Abs (e.g., Anti‐ubiquitin Abs), various biomarkers for selective acrosome damage like glycans binding lectins like Pisum satium agglutinin (PSA), Peanut agglutinin (PNA) and Lens cullinaris have been used for nano‐purification of semen and other procedures (Bisla, Rautela, et al, 2020; Bisla, Rautela, et al, 2021; Odhiambo et al, 2014). Several types of NPs have been used as an antioxidant, as well as for their antimicrobial properties thus paving the way for the spermatozoa quality and male fertility assessment and improvement.…”
Section: Introductionmentioning
confidence: 99%